Biological Activities of Nanomaterials (Bufadienolides, Peptides and Alkoloids) in the Skin of Amphibian on Gammarus Pulex L. - Bayazit, V. (My University, 2010)
The purpose of this sudy was to examine the toxic effects of bufadienolides of antimicrobial peptides and alkoloids on Gammarus pulex L.(Crustacea:Amphipoda:Gammaridae) Bufadienolides (Arenobufagin, Arenobufagin hemisuberate, Arinobufagin 3- sulfate, Bufalin, Bufalin hemisuberate, Bufoatlin 3-sulfate, Bufotalinin, Bufotalone, Cinobufagin, Cinobugagilon, Cinobufotalin, Desacetylcinobufagin, Gamabufotalin hemisuberoate, Gamabufotalin3-sulfate,15-hydroxybufalin, 19-hydroxybufalin, Marinobufagin, Marinoic acid, Marinosin and Resibufaginol), Amphibian peptides (Caerin 1.1, Caerin 1.9, Caerin 4.1, Dahlein 5.6, Dermaseptin, Esculentin-1ARb, Esculentin-2P, Maculatin 1.1, Magainin II, MRP, Palustrin-3AR, Ranatuerin-6, Ranatuerin-2P, Uperin 3.6, RCCP) and Alkoloids (Samandarine, Batrachotoxin, Histrionictoxin, Pumiliotoxin, Allopumiliotoxin, Homopumiliotoxin, Decahydroquinoline, Epibatidine) killed significantly the animals in the experimental groups (p< 0.01).
Keywords: Amphibian peptides and alkoloids Gammarus pulex; Bufadienolides